2021
DOI: 10.1016/j.iccn.2020.102967
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on nursing time in intensive care units in Belgium

Abstract: Introduction The COVID-19 pandemic has had a significant impact on nursing practice in intensive care unit (ICU) and, consequently, on workload. Objective To assess the nurse-patient (N:P) ratio required by COVID-19 patients and to identify the factors that influence nursing in this context. Design This study was a retrospective observational study that evaluated the N:P ratio using the Nursing Activities Score (NAS). Setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
120
1
38

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(168 citation statements)
references
References 35 publications
9
120
1
38
Order By: Relevance
“…The workload of the respiratory care was higher, which is in line with the higher number of ventilated COVID-19 ICU patients. The increase of workload in the category ‘Performing mobilization procedures with three or more nurses with any frequency’ can be explained by the frequency of turning patients into prone- or supine position as this became standard in the treatment of COVID-19 ICU patients ( Bruyneel et al, 2021 , Azoulay, 2020 , Coppo et al, 2020 ). We also found a difference in workload in the support and care of the patient and his or her relatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The workload of the respiratory care was higher, which is in line with the higher number of ventilated COVID-19 ICU patients. The increase of workload in the category ‘Performing mobilization procedures with three or more nurses with any frequency’ can be explained by the frequency of turning patients into prone- or supine position as this became standard in the treatment of COVID-19 ICU patients ( Bruyneel et al, 2021 , Azoulay, 2020 , Coppo et al, 2020 ). We also found a difference in workload in the support and care of the patient and his or her relatives.…”
Section: Discussionmentioning
confidence: 99%
“…The nursing workload of patients with COVID-19 pneumonia was perceived high compared to the average patient admitted to the ICU. Recent research showed that in Italy and Belgium the nursing workload as expressed with the Nursing Activities Score was higher in patients with COVID-19 compared to other ICU patients ( Lucchini et al, 2020 , Bruyneel et al, 2021 ). Moreover, due to the pressure on ICU beds there was no capacity left for planned surgical patients with a need for postoperative care on the ICU ( Dutch COVID-19, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have highlighted the diagnosis, clinical characteristics and treatment, 3 and the disease prevalence 27 . Other studies have discussed the seriousness of psychological issues on medical personnel 28,29 and the importance of providing psychological help for them 30 . Few studies have been conducted regarding the experiences of critical care nurses caring for individuals infected by COVID‐19 in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…As of December 2020, more than 18 million individuals had been infected with COVID-19 in Europe and around 412,000 had died [ 1 ], of which 17,000 were in Belgium [ 2 ]. The pandemic had had a serious impact on hospital burden and on the working conditions and mental health of healthcare professionals (HCPs) [ 3 , 4 , 5 ]. Yet vaccination was under way, with the first COVID-19 vaccines being evaluated and approved by the European Medicines Agency and the European Commission, and national and international vaccination strategies being developed.…”
Section: Introductionmentioning
confidence: 99%